Caller characteristics influence recruitment to collective anti-predator events in jackdaws - Richard D. Woods (Nature Portfolio, 2018)
Abstract Across the animal kingdom, examples abound of individuals coming together to repel external threats. When such collective actions are initiated by recruitment signals, individuals may benefit from being selective in whom they join, so the identity of the initiator may determine the magnitude of the group response. However, the role of signaller discrimination in coordinating group-level responses has yet to be tested. Here we show that in wild jackdaws, a colonial corvid species, collective responses to anti-predator recruitment calls are mediated by caller characteristics. In playbacks next to nestboxes, the calls of nestbox residents attracted most recruits, followed in turn by other colony members, non-colony members and rooks (a sympatric corvid). Playbacks in fields outside nestbox colonies, where the immediate threat to broods was lower, showed similar results, with highest recruitment to nearby colony members’ calls. Responses were further influenced by caller sex: calls from non-colony member females were less likely to elicit responsive scolding by recruits than other calls, potentially reflecting social rank associated with sex and colony membership. These results show that vocal discrimination mediates jackdaws’ collective responses and highlight the need for further research into the cognitive basis of collective actions in animal groups.